Logistics 4.0 toward circular economy in the agri-food sector - Mladen Krstić; Giulio Paolo Agnusdei; Pier Paolo Miglietta; Snežana Tadić (Sustainable Futures, 2022)
Technological development, automation, digitalization, networking, new forms of communication, etc. initiated a new industrial revolution, also known as Industry 4.0. It represents a new form of organization and control of the value chain in the product life cycle. It is a concept that is intensively changing production processes, but its effects are also visible in other areas of human activity, primarily trade, health, agriculture, logistics, etc. By applying the solutions and technologies of Industry 4.0 in the field of logistics, the concept of Logistics 4.0 was developed with the aim of achieving greater efficiency of logistics systems and processes. On the other hand Circular Economy is a model of production and consumption, which involves sharing, leasing, reusing, repairing, refurbishing and recycling existing materials and products as long as possible, whose efficiency greatly depends on the logistics activities and processes. Having previous in mind, the subject of this paper is to rank the main interest areas of circular economy in terms of applying the industry 4.0 technologies for performing the logistics activities within the agri-food sector. The aim is to determine the area which has the greatest potential for further development and should thus be in focus of the future planning of industry 4.0 based logistics activities in the agri-food CE context. Since the circular economy is a systemic approach to economic development designed to benefit businesses, society, and the environment, this is a multi-criteria decision making (MCDM) problem. For solving it a hybrid MCDM model combining the Analytical Hierarchy Proces (AHP) method for establishing the criteria weights, and the Comprehensive distance-Based RAnking (COBRA) method for the final ranking of the alternatives, is proposed. The results indicate that the most important CE interest areas are Reuse/Remanufacturing/Recycle, Supply Chain Management and Product Lifecycle Management.